Informal Learning Engagement In Selected Malaysian SMEs - Victoria, Jonathan; Lim, Agnes; Dayang Kartini, Abang Ibrahim (2011)
This study was conducted to contribute to the understanding of informal learning engagement in SMEs in Malaysia. Specifically, this study identified the different types of informal learning activities preferred by employees and their level of engagement. The research examined factors influencing informal learning engagement and which factor influences informal learning engagement the most. SMEs are the growing force for a country’s economy and continuous development of its human resource is vital to ensure its sustainability. This study was based on a sample survey of 171 employees from 38 SMEs from various sectors. The findings indicated a medium level of informal learning engagement. Individual and organizational factors were correlated with informal learning engagement. Results from multiple regression analysis indicated that individual factors are best predictors of informal learning engagement. The results further give light to how informal learning may be encouraged and developed in the Malaysian SMEs.